Economic Determination of Modified Multiple Dependent State Sampling Plan under Some Lifetime Distributions. (29th January 2021) - Aslam, Muhammad; Jeyadurga, P.; Balamurali, S.; Azam, Muhammad; AL-Marshadi, Ali
Abstract : In this paper, the modification of multiple dependent state sampling plan is proposed and designed for assuring a mean lifetime of the products under Birnbaum–Saunders distribution and Weibull distribution. The optimal parameters of the proposed plan are determined based on two points on the operating characteristic curve approach. Different combinations of producer's risk and consumer's risk are considered for plan parameters determination. The efficacy of the proposed plan is compared with those of other existing sampling plans using an average sample number and operating characteristic function. The economic designing of the proposed plan is also considered and the comparative study is done based on the total cost of the inspection.